Seleksi Fitur Dengan Particle Swarm Optimization Untuk Pengenalan Pola Wajah Menggunakan Naive Bayes (Studi Kasus Pada Mahasiswa Universitas Brawijaya Fakultas Ilmu Komputer Gedung A) - Satria Habiburrahman Fathul Hakim; Imam Cholissodin; Agus Wahyu Widodo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
The Presence system of students in the Faculty of Computer Science, Brawijaya University is still using the manual system that is very prone to be misused by the students as entrusted that presence to his friend. Therefore we need a system that has been digitized and also fast in finding solution problem. Optimization method is a method of searching for faster solutions. For this time the researchers is using the Particle Swarm Optimization (PSO) method, that method was inspired by the social behavior of bird movements in their daily lives. While the method of classification is a method that is closely related to the probability hypothesis. So there are 2 methods and have different functions in facial recognition at the student presences where PSO here is as a feature selection and Naive Bayes here as a classification engine as well as a function to get fitness. In the test results obtained that iteration with the best total fitness value is on the number of particles 38 with the highest total fitness is 13,38, then on testing the effect of the number of iterations obtained the conclusion that the largest total fitness is at iteration 190 is 36,799, in other words the greater of iteration the fitness is also better and the last test is on testing for the weight of inertia is 1,2 with the highest total fitness result is 1,588.